Isoorientin ameliorates osteoporosis and oxidative stress in postmenopausal rats. (31st December 2022) - Cao, Zhilin; Liu, Wei; Bi, Benjun; Wu, Hao; Cheng, Gong; Zhao, Zhongyuan
Abstract: Context: Isoorientin has many biological activities, including antioxidant, anti-inflammatory, antitumor. However, the effect of isoorientin on postmenopausal osteoporosis remains unclear. Objective: To evaluate the effect of isoorientin on postmenopausal osteoporosis. Materials and methods: Sprague-Dawley rats were divided into five groups ( n = 5): sham, model, 17-β-oestradiol (E2, 10 μg/kg/day), low-dose isoorientin (L-Iso, 50 mg/kg), and high-dose isoorientin (H-Iso, 100 mg/kg). The rats were ovariectomized, treated by gavage daily for 12 weeks, and serum and femur samples were collected. Bone mineral density, bone metabolism, and oxidative stress were assessed. H&E staining, immunohistochemistry, and western blotting were employed. Results: Isoorientin improved the bone mineral density of the lumbar vertebrae (2.01 ± 0.05 g/cm 3 in H-Iso group vs. 1.74 ± 0.07 g/cm 3 in model group) and femur (1.46 ± 0.06 g/cm 3 vs. 1.19 ± 0.03 g/cm 3 ), increased the trabecular bone number (1.97 ± 0.03 vs. 1.18 ± 0.13) and thickness (0.27 ± 0.02 vs. 0.16 ± 0.03 mm). Isoorientin decreased the separation degree of trabecular bone, ameliorated bone histomorphology changes, and significantly improved the mechanical properties. Isoorientin diminished MDA (by 60%) and increased SOD (by 49.2%), and GSH-Px (by 159%) activity. Furthermore, osteoprotegerin (OPG), nuclear factor erythroid 2-like 2 (Nrf2), haem oxygenase (HO-1), NAD(P)H quinone dehydrogenase 1(NQO1), and oestrogen receptor 1(ESR1) protein expression increased, while receptor activator of nuclear factor-κB ligand (RANKL) protein expression decreased after treatment. Conclusions: Isoorientin ameliorates osteoporosis via upregulating OPG and Nrf2/ARE signalling, suggesting isoorientin maybe a potential therapeutic drug for PMOP.